1998
DOI: 10.1007/s004410051143
|View full text |Cite
|
Sign up to set email alerts
|

Presence and location of endothelin and endothelin-binding sites in human nasal mucosa under normal and metaplastic conditions

Abstract: The presence and site of production of endothelin-1 (ET-1) was investigated in biopsies obtained from the nasal mucosa of 10 healthy human subjects and 10 patients affected by chronic rhinitis. The presence and localization of receptors for ET-1 was also investigated. Bioptic fragments were examined by scanning electron microscopy. ET-1 was present in the vessels and in the respiratory epithelium of normal subjects, whereas in patients affected by epithelial metaplasia induced by chronic rhinitis, it was absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The current demonstration of ET A -and ET B -receptor mRNA in the human nasal mucosa agrees well with a recent report using in situ binding to demonstrate the location of these receptors in nasal vessels (21). It was observed that the ET A -receptor was predominantly expressed in the vascular walls, whereas ET B -receptors were more abundant in the epithelium.…”
Section: Discussionsupporting
confidence: 92%
“…The current demonstration of ET A -and ET B -receptor mRNA in the human nasal mucosa agrees well with a recent report using in situ binding to demonstrate the location of these receptors in nasal vessels (21). It was observed that the ET A -receptor was predominantly expressed in the vascular walls, whereas ET B -receptors were more abundant in the epithelium.…”
Section: Discussionsupporting
confidence: 92%
“…The cavernous tissue counteracts the widening nasal air passage (Cauna and Hinderer 1969;Gulisano et al 1998) so that there is only slow decline of nasal resistance with age (Eccles 2000). According to Hinderer (1975) and Cauna (1982), progressive dryness of the mucosa as a part of the aging process is the result of reduction or damage of subepithelial capillaries and of fluid supply by transudation due to evaporation from the mucus blanket exceeding the resupply of fluid.…”
Section: High Incidence Of Squamous Metaplasiamentioning
confidence: 99%
“…In human nasal mucosa, ET was first reported in the endothelial cells of both capacitance and resistance blood vessels [ 12]. Both immunoreactive ET‐1 and endothelin‐converting enzyme (ECE)‐1 are expressed in epithelial and endothelial cells, submucosal glands (in mucous cells and to a greater extent in serous cells), inflammatory cells (macrophages), and blood vessels such as arterioles, small veins and venous sinusoids of human nasal mucosa [ 13–17] ( Table 1). These findings contrast with the distribution of other peptides such as calcitonin gene‐related peptide (CGRP), neuropeptide Y (NPY), gastrin‐releasing peptide (GRP), vasoactive intestinal polypeptide (VIP), substance P (SP), and neurokinin A (NKA), which are mainly present in bundle nerves involved in adrenergic, cholinergic and nonadrenergic, noncholinergic functions [ 18–21].…”
Section: Et Immunoreactivitymentioning
confidence: 99%
“…ET‐1 binding sites are found concentrated around submucosal glands, arterioles and venous sinusoids, but not in the epithelium of human nasal mucosa [ 13, 17]. Although early studies done on animal lower airways reported ET‐specific binding sites in the epithelium [ 10], no constitutive binding sites have been found in the human nasal epithelium.…”
Section: Et Receptorsmentioning
confidence: 99%
See 1 more Smart Citation